Geochemistry of Hydrothermal Alteration in Volcanic Rocks - Marfil, Silvina Andrea (2012)
Minerals where a hydrothermal fluid delivers the chemical reactants and removes the aqueous reaction products. An understanding of hydrothermal alteration is of value because it provides insights into the chemical attributes and origins of ore fluids and the physical conditions of ore formation (Reed M. 1997).Within a mineral deposit, the solution channel ways are usually obvious because precipitated minerals and altered wall rocks remain as evidence. The direction in which the solutions flowed, especially in flat-lying deposits, is usually less obvious but in many cases can be enferred from mineral zoning or similar evidence.